LAPORAN HASIL PRAKTIK PROFESI ASUHAN KEPERAWATAN KOMUNITAS DI RT 01 DAN RT 02 KELURAHAN PERIUK KECAMATAN PERIUK KOTA TANGERANG PADA TANGGAL 12 JUNI-08 JULI 2023 - Alfika safitri; Muhamad Dian Permana Angga Dirja; Suci Ririn Puspita; Kasifah; Nurul Siti Khodijah; Rika Apriliana; Hesty Oktalia; Yulia Sartika Sari; Annisa Rahmawati; Tasya Rezky Amelia; Riska Elda Sari; Tuti Selfiani; Dewi Puji Astuti; Lingling Rahmawati (Yayasan Nusantara Hasana Berdikari, 2023)
Community is a social group that lives in a place, interacts with each other, knows each other and has the same interests and interests (WHO). Community is a group of people who live in the same location under the same government, the same area or location where they live, social groups that have the same interests. In the implementation of public health services focused on improving health in community groups. To improve the degree of public health, it can be started from individuals, groups to the RT and RW levels. In the area of ​​RW 01, Periuk Village, Tangerang City, there are 6 RTs with a total sample of 780 families. Regional characteristics and health problems that arise in RW 01, namely information on prevention and diet for hypertension, gout arthritis and diabetes mellitus. To carry out this task, a nurse who is competent in providing community nursing care is needed. Experience in addition to knowledge is needed to obtain optimal results. One way to gain experience is through practicing community nursing at RT 01 and 02 in RW 01 Periuk Village, Tangerang City.